PERBANDINGAN PEMILIHAN GUBERNUR DI INDONESIA DAN FILIPINA: Comparison of Governor Elections in Indonesia and the Philippines - Alviansyah; Ninuk Wijiningsih (AMICUS CURIAE, 2025)
The Philippines is a democratic country in Asia. The Republic of Indonesia has similarities and differences with the Republic of the Philippines. The main problem discussed in this research is what are the differences and similarities in gubernatorial elections in Indonesia and the Philippines? and what are the advantages and disadvantages of gubernatorial elections in Indonesia and the Philippines? The research was conducted using normative legal research methods, with secondary data supported by primary data. The nature of the research is descriptive and conclusions are drawn using a deductive method. Based on the research results, there are similarities regarding the gubernatorial election, namely that they are both elected by the people where there are polling places (TPS), the leadership area is equivalent to the province, and the difference is that candidates for governor in the Philippines are required to stay in the area they will lead for 6 months while in Indonesia they do not. . Apart from that, the advantage of the gubernatorial election in Indonesia is that the timing of the regional elections with elections is different. The advantage of the gubernatorial election in the Philippines is that the votes are counted using machines.